Processus Bernardi Delitiosi: The Trial of Fr. Bernard Delicieux, 3 September - 8 December 1319. - Friedlander, Alan (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Book Research and Testimony Before the House Subcommittee on International Law and Immigration and Refugees, October 2, 1991. - Hamilton-Merritt, Jane (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Failure of Democracy Movement: Human Rights in the People's Republic of China, 1988/89 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1991)
Keywords: China; China; China; Civil rights; History; Human rights; Tiananmen Square Incident; 1989; dept.his; faculty_collection

Book Review: Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.) - Mintz, Max M. (Journal of American History, 1991)
Max M. Mintz; Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.), Journal of American History,
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991GF12400029 tex.unique-id: [object Object]
Keywords: book.review; dept.his

Save the babies - american public-health reform and the prevention of infant-mortality, 1850-1929 - meckel,ra - Quiroga, VAM (Journal of American History, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991FP54300084
Keywords: dept.his; peer-reviewed